Knowledge, attitudes and practices of breast feeding among lactating mothers in a tertiary care hospital in Dakshina Kannada district: a cross sectional survey - S., Pramodha M.; Pitty, Nikita; S., Chaitra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Breastfeeding plays a crucial role in the general health and wellbeing of infants. However, this fact has been made to look inconsequential due to various misconceptions and lack of adequate knowledge among lactating mothers. The aim of this study was to assess the knowledge, attitudes and practices of breastfeeding among postnatal women in Dakshinakannada district of Karnataka, India. The objective was to educate them and encourage breastfeeding. Methods: This study is a cross-sectional survey conducted during a period of 2 months from November to January 2019 among 80 postnatal mothers regarding their KAP of breastfeeding. A questionnaire was designed from FAO guidelines for assessing nutrition-related knowledge, attitudes and practices manual and The Iowa Infant Feeding Attitudes. The data was collected by a single interviewer, collaborated into a 3-point Likert scale and analyzed using descriptive statistics. Results: The study shows that 81.25% of the mothers had good knowledge regarding breastfeeding, but the alarming finding was that 46.6% of them had a neutral attitude towards it. Conclusions: The study showed that there is significant possibility for enhancing breastfeeding practices among lactating mothers by simple provision of supportive prenatal and postnatal counselling. The role played by healthcare workers in this context would be very imperative to accomplish millennium development goals of reducing infant mortality.